Per una futura nuova edizione della Bibbia gotica. Problemi e prospettive - Carla Falluomini (Filologia Germanica)
Modern methods of reading palimpsests and new databases of biblical variants permit us to re-examine the extant Gothic manuscripts and texts with a view to preparation of a new edition of the Gothic Bible. The purpose of the present paper is to highlight some methodological aspects of this project: the importance of investigating (1) the cultural milieu in which the Gothic translator worked and (2) the textual tradition of the Bible in determining the Greek model for the Gothic version and any subsequent changes which may have been made to it. The Gothic text is one of the earliest examples of the Koine type and it may preserve ancient readings not transmitted in late Byzantine manuscripts.